9‐Ethynyl noscapine induces G2/M arrest and apoptosis by disrupting tubulin polymerization in cervical cancer. Issue 3 (6th October 2021) - Nagireddy, Praveen Kumar Reddy; Kumar, Dinesh; Kommalapati, Vamsi Krishna; Pedapati, Ravi Kumar; Kojja, Venkateswarlu; Tangutur, Anjana Devi; Kantevari, Srinivas
Abstract: Noscapine is a phthalide isoquinoline alkaloid present in the latex of Papaver somniferum and has demonstrated potent antitumor activity in various cancer models. Structural changes in the core molecule of noscapine architecture have produced a number of potent analogs. We have recently synthesized the novel noscapine analogs (3, 4, and 5 ) with different functional groups appended at ninth position of natural noscapine. The anticancer activity of these compounds has been investigated using various human cancer cell lines such as HeLa (cervical cancer), DU‐145 (prostate cancer), MCF‐7 (breast cancer), and IMR‐32 (neuroblastoma). One of the compounds in this series, 9‐ethynyl noscapine (5 ), has demonstrated good anticancer activity against HeLa cells. Biological studies demonstrated that compound 5 decreased cell viability and colony formation in HeLa cells in a concentration dependent manner. To further uncover the mechanism in detail, we evaluated compound 5 effect on cell cycle progression, microtubule dynamics, and apoptosis. Cell cycle and western blotting analysis revealed that 9‐ethynyl noscapine treatment resulted in cell cycle arrest at G2/M and decreased CDK1 and cyclinB1 protein expression. We also observed that 9‐ethynyl noscapine (5 ) treatment leads to disruption in tubulin polymerization and induction of apoptosis by decreasing expression of bcl2, pro‐caspase 3, and activation of cytochrome C. Taken together, our results indicate that 9‐ethynyl noscapine (5 ) effectively supresses the growth of cervical cancer cells (HeLa) by disrupting tubulin polymerization, cell cycle progression leading to apoptosis.